Step adjustment in long jump approach in beginner athletes aged 12-13 - Panteli, F.; Theodorou, A.; Smirniotou, A. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
This study examined whether young non-expert long jumpers showed at the long jump approach (LJA) similar pattern of variability in footfall placement across trials as adult expert athletes. The LJA of 51 competition jumps performed by 17 athletes, aged 12-13 years, were analyzed. A stride regulation pattern emerged on the 5th and 4th stride prior to take-off and at a mean distance of 8.7m (males) and 7.2m (females) from take-off board. TBD variability reached a maximum value of 32.1±19.9cm and 37.4±29.9cm and was finally reduced to 10.6±16.1cm and 15.6±14.4cm for males and females respectively. The striding pattern was similar to that reported in the literature for adults. However, beginners were found to be less consistent over the initial phase of the LJA than adult athletes and made more dramatic step length modifications during the final two strides.